Educação musical: construção da profissionalidade docente no Programa Guri Santa Marcelina - Albuquerque, Rosana Olivares De [UNIFESP] (2019)
This body of work presents the results of a qualitative study intended to investigate the role of music educators and how they perceive the evolution of their profession in the field of unofficial music education. This research gathers learnings from official documents of Guri Santa Marcelina, a public initiative designed to popularize music education among children and teenagers, during the mandates between 2013 and 2017. Moreover, semi-structured interviews were conducted with four music teacher aiming to gain a deeper understanding of their musical learning paths, gaps and demands. A dialogue between the subjects of music and education leads the thematic of the professional role of music teachers with or without a formal education, calling attention to the process of forming qualified music teachers. To explore this matter that encapsulates the complexity of formal music education for both, students and teachers and the learning environment, this study is grounded in Pierre Bourdieu’s (1977, 1979, 2007) work that examines the cultural capital concept, Roger Chartier’s (1988, 2009, 2018) studies about the representation and Maurice Tardif’s (2000, 2002, 2014) contribution on the formal education of teachers.